Ustalone Procesy Tłoczenia Cienkościennych Naczyń Walcowych - Marciniak, Z. (Engineering Transactions, 1959)
The paper contains an analysis of steady-state processes of pressing thin-walled cylindrical shells such as tubes, cylinders, cylindrical walls of vessels etc.; the changes of thickness of the wall taking place during the process are-taken into consideration, as also the changes of the yield point due to the phenomenon of strain-hardening of the metal. This analysis is based on the energy balance of the process, from which the stress distribution along the generant of the shell is obtained. Conclusions are drawn concerning the deformation process of the material and its final form. Several diagrams enable the determination of the forces and the final dimensions for brass shells.